The efficacy and safety of epirubicin and cyclophosphamide combined with pyrotinib in neoadjuvant treatment for HER2-positive breast cancer: A real-world study - Li, Fu; Liang, Yimin; Luo, Ming; Shen, Jiayue; Zhou, Taosheng; Liang, Yajing; Tang, Xiaoqi; Yuan, Huiming; Zeng, Jian (Frontiers in Oncology, 2023)
Abstract Purpose: Long-term survival benefit of anthracyclines for human epidermal growth factor receptor 2 (HER2)-positive breast cancer is clear. In the neoadjuvant treatment, compared with the monoclonal antibody such as trastuzumab and pertuzumab, the clinical benefit of pyrotinib, a new small-molecule tyrosine kinase inhibitor (TKI), as the main anti-HER2 strategy currently requires more research to determine. Our real-world study is the first prospective observational study in China to evaluate the efficacy and safety of epirubicin (E) and cyclophosphamide (C) with pyrotinib as anti-HER2 therapy in the neoadjuvant setting of patients with stage II-III HER2-positive breast cancer. Methods: From May 2019 to December 2021, 44 untreated patients with HER2-positive nonspecific invasive breast cancer who received 4 cycles of neoadjuvant EC with pyrotinib. The primary endpoint was pathological complete response (pCR) rate. Secondary endpoints included the overall clinical response, breast pathological complete response rate (bpCR), the rate of axillary lymph nodes pathological negativity and adverse events (AEs). Other objective indicators were the rate of surgical breast-conserving, the negative conversion ratios of tumor markers. Results: Thirty-seven (84.1%) of 44 patients completed this neoadjuvant therapy, and 35 (79.5%) had surgery and were included in the primary endpoint assessment. The objective response rate (ORR) of 37 patients was 97.3%. Two patients reached clinical complete response, 34 obtained clinical partial response, 1 sustained stable disease, and no one had progressive disease. Eleven (31.4%) of 35 patients who had surgery achieved bpCR and the rate of axillary lymph nodes pathological negativity was 61.3%. The tpCR rate was 28.6% (95% CI: 12.8-44.3%). Safety was evaluated in all 44 patients. Thirty-nine (88.6%) had diarrhea, and 2 developed grade 3 diarrhea. Four (9.1%) patients had grade 4 leukopenia. All grade 3-4 AEs could be improved after symptomatic treatment. Conclusion: The regimen of 4 cycles of EC combined with pyrotinib presented some feasibility in the neoadjuvant setting for HER2-positive breast cancer with manageable safety. new regimens with pyrotinib should be evaluated for higher pCR in future.